2011
DOI: 10.1038/npp.2011.32
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin Influences Insula and Amygdala Activation During Anticipation of Emotional Images

Abstract: Pregabalin (PGB) has shown potential as an anxiolytic for treatment of generalized and social anxiety disorder. PGB binds to voltagedependent calcium channels, leading to upregulation of GABA inhibitory activity and reduction in the release of various neurotransmitters. Previous functional magnetic resonance imaging (fMRI) studies indicate that selective serotonin reuptake inhibitors and benzodiazepines attenuate amygdala, insula, and medial prefrontal cortex activation during anticipation and emotional proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 70 publications
6
36
1
Order By: Relevance
“…Several areas of the brain are involved in pruritus processing and perception, such as the primary sensory cortex, prefrontal cortex, premotor areas, cerebellum, anterior cingulum, and dorsal insular cortex [12]. Substances such as pregabalin and gabapentin have been described to inhibit calcium currents via high-voltage-activated channels containing the a2d-1 subunit, to reduce the release of various neurotransmitters and to attenuate amygdala and insula activation in the central nervous system, possibly resulting in suppression of itch neuron activity [13,14]. The concept of interfering with pruritus transmission and perception was successful in 71.3% of patients treated in the third step (29.6% of the total cohort).…”
Section: Discussionmentioning
confidence: 99%
“…Several areas of the brain are involved in pruritus processing and perception, such as the primary sensory cortex, prefrontal cortex, premotor areas, cerebellum, anterior cingulum, and dorsal insular cortex [12]. Substances such as pregabalin and gabapentin have been described to inhibit calcium currents via high-voltage-activated channels containing the a2d-1 subunit, to reduce the release of various neurotransmitters and to attenuate amygdala and insula activation in the central nervous system, possibly resulting in suppression of itch neuron activity [13,14]. The concept of interfering with pruritus transmission and perception was successful in 71.3% of patients treated in the third step (29.6% of the total cohort).…”
Section: Discussionmentioning
confidence: 99%
“…The STIMEX is a continuous performance task that has reliably activated the anterior insula in prior studies (Simmons et al, 2006;Aupperle et al, 2011). The STIMEX assesses the impact of anticipating affective stimuli on attention to a response signal and on the subsequent response ( Figure 1) (Simmons et al, 2006).…”
Section: Stimulus Expectancy Task (Stimex)mentioning
confidence: 99%
“…Square frames were presented every two seconds. The number of consecutively cued trials presented prior to presentation of an affectively valenced picture varied from picture to picture jittering trials on which affectively loaded stimuli were presented (Aupperle et al, 2011). Two versions of the STIMEX were administered to each subject during each session.…”
Section: Stimulus Expectancy Task (Stimex)mentioning
confidence: 99%
See 1 more Smart Citation
“…These effects vary among AEDs [67,68] and depend on the specific task performed during the measurements [69]. While AEDs mainly attenuate the activation patterns, as can be expected from their mechanisms of action, also enhanced activation during AED use has been reported [70]. This seemingly contradictory result could be an indirect effect of attenuated activation in other brain areas, or result directly from AED mechanisms, as a computer simulation showed that modulation of the sodium channels by phenytoin or carbamazepine can also lead to increased excitation [71].…”
Section: Functional Mrimentioning
confidence: 98%